Analysis of some anti-depressant drugs in aqueous samples using agarose film micro-electro driven membrane extraction - Mohamad Hanapi, Nor Suhaila (2015)
Agarose film micro-electrodriven membrane extraction (AF-µ-EME) combined with liquid chromatography as a new microextractiontechnique was developed and applied for extraction of three selected anti-depressant drugs from tap water and human urine samples.Using 2-nitrophenyl octyl ether, NPOE as organic liquid membrane immobilized in the pores of a porous agarose film allowed the extraction of selective analytes from acidic sample solution into the acceptor phase. Different influencing parameters such selection of organic liquid membrane, sample pH, salt addition, extraction time and applied voltage were optimized.Under the optimal extractions conditions, the method demonstrated good linearity in the range of 0.5-500 µg L-1 withgood correlation of determination r2 ge; 0.9979,low limits of detection (0.02- 0.20 µg L-1), high enrichment factors (110-142), good relative recoveries in the range of (87-109.1%) and satisfactory precisions with RSDs of